Power Relations and Criminal Law Challenges in Addressing Sexual Violence in Indonesian Educational Institutions - Thalia Ongko Wijoyo; Kenneth Kenneth (Journal Kompilasi Hukum, 2025)
Sexual violence in educational institutions has emerged as a persistent and complex problem in Indonesia, reflecting the intersection of unequal power relations, institutional culture, and gaps in legal enforcement. This paper examines the issue from a criminal law perspective, focusing on case studies involving universities, Islamic boarding schools, and private tutoring settings. Using a normative juridical approach, the study analyzes legal documents, judicial decisions, and secondary literature to evaluate how Indonesian criminal law addresses sexual violence in education. The findings show that, although Indonesia has recently adopted progressive legislation and established institutional mechanisms such as task forces for prevention and handling, the implementation remains fragmented and often fails to provide adequate protection to victims. Case studies, including the widely discussed Agni case at Universitas Gadjah Mada and the high-profile Herry Wirawan case, highlight recurring patterns of institutional reluctance, victim blaming, and weak accountability structures. Comparative insights from Title IX in the United States and the Sexual Offences Act in the United Kingdom demonstrate that mandatory reporting obligations, trauma-informed procedures, and institutional accountability frameworks are crucial in bridging the gap between legal norms and practice. This study concludes that Indonesia requires a more integrated criminal law policy that strengthens enforcement, mandates institutional responsibility, and prioritizes victim-centered approaches to effectively address sexual violence in educational settings.